Do Myocardial Blush Grade Following Chronic Total Occlusion Recanalization Improve Clinical Outcome of Chronic Coronary Syndromes Patients? - Ikhwan Handirosiyanto; Dadang Hendrawan; Djanggan Sargowo; Yoga Waranugraha; Fahmi Rusnanta; Ardhani Galih Prakoso; Mohammad Saifur Rohman (Universitas Brawijaya, 2020)
Background : Myocardial blush grade (MBG) is an angiographic parameter to describe the adequacy of myocardial reperfusion. The correlation between myocardial blush and the clinical outcome following chronic total occlusion (CTO) recanalization is still unclear. Our study aimed to investigate the impact of myocardial blush after CTO recanalization on the clinical outcome of CCS patients.Design : A retrospective cohort study was conducted. Patients who underwent CTO recanalization were divided into two groups based on the myocardial blush. Patients were classified as having good myocardial blush (MBG category 2 to 3 or QUBE 0 to 10.2) and poor myocardial blush (MBG category 0 to 1 or QUBE 10.2 to 36.4). The outcome measured was the improvement of angina measured using the Seattle Angina Questionnaire (SAQ) and the reduction of antianginal drug regimens.Results : The follow-up period was ranging from 2 to 24 months following the CTO recanalization procedure. The SAQ for physical limitation (83.86 ± 16.11 vs. 77.92 ± 3.44; p = 0.247), angina frequency (85.27 ± 17.44 vs. 74.76 ± 22.05; p = 0.105), and quality of life (73.24 ± 3.41 vs. 72.82 ± 3.56; p = 0.932) between the two groups was not significantly different. Good myocardial blush was not correlated with the reduction of antianginal drug regimens (10 (52.6) vs. 8 (40); p = 0.639).Conclusion : Myocardial blush post-CTO recanalization was not associated with the improvement of angina symptoms and the reduction of antianginal drug regimens among patients with CCS.